BUKIT LAWANG ECOTOURISM DIGITAL CAMPAIGN IN CULTIVATING ECOCENTRISM ETHICS FOR MEDAN CITY RESIDENTS - Dzulhajj ‘Aeyn Abe Siregar (OPINI: Journal of Communication and Social Science, 2025)
Bukit Lawang, located within Gunung Leuser National Park and characterized by an ecocentric lifestyle, has the potential to influence urban communities through social media. According to the United Nations Educational, Scientific and Cultural Organization (UNESCO), Gunung Leuser National Park is home to approximately 10,000 plant species, 580 bird species, and key mammals such as Pongo (orangutans), tigers, rhinoceroses, elephants, and sun bears (UNESCO, 2024). This study adopts an interpretative paradigm. Data are collected through content analysis and literature review methods. Recent studies that are directly and indirectly related to the destination objects namely Bukit Lawang, Instagram, YouTube, and websites are thematically examined through descriptive presentation. There are several travel agency service blogs, such as sumatra-orangutan-explore.com, bukitlawang.com, bukitlawangguide.com, orangutan-trekking.com, and others. These travel agencies are managed by professionals who understand marketing communication and package information about Bukit Lawang in ways that effectively encourage prospective international users to purchase their services.